Impact of Chikungunya fever on daily life activities of elderly people (Research, Society and Development, 2020)
Objective: to evaluate the impact of Chikungunya Fever on the daily life activities (AVDs) of elderly people. Method: exploratory study conducted in 2019 in Redenção-CE/Brazil, with 248 elderly people accompanied by Family Health Centers. The data were collected with a structured instrument that contained demographic variables, clinical and with the Katz Scale. The analysis of the data occurred from the chi-square test of Pearson. Results: there was a predominance of elderly women (73.79%) with a mean age of 71 years and low level of education (85.48%). There was a statistically significant association between joint dysfunction and limitation for AVDs. The main basic activity performed with limitations was transference (63.9%) and 23.7% of the elderly were considered partially dependent and 53.8% totally dependent in basic activities. All instrumental activities were performed with limitations. Conclusion: It was found that Chikungunya Fever infection negatively impacted the function of the elderly. Thus, nursing care planning needs to be based on practices that mitigate the effects of the disease's sequelae on these patients' quality of life.